2020
DOI: 10.3390/ijerph17062026
|View full text |Cite
|
Sign up to set email alerts
|

High Variability in Sepsis Guidelines in UK: Why Does It Matter?

Abstract: It is recommended that developers of Point Of Care Tests (POCTs) assess the care pathway of the patient population of interest in order to understand if the POCT fits within the pathway and has the potential to improve it. If the variation of the pathway across potential hospitals is large, then it is likely that the evaluation of effectiveness is harder and the route towards large-scale takes adoption longer. Evaluating care pathways can be a time-consuming activity when conducted through clinical audits or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Our result for data extraction was very satisfactory. Other studies also indicated that data extraction errors occur regularly leading to biased estimates [26][27][28], while this will usually not impact the conclusions of the SR [29,30]. One exception was the extraction on RoB ratings from the original publication.…”
Section: Discussionmentioning
confidence: 99%
“…Our result for data extraction was very satisfactory. Other studies also indicated that data extraction errors occur regularly leading to biased estimates [26][27][28], while this will usually not impact the conclusions of the SR [29,30]. One exception was the extraction on RoB ratings from the original publication.…”
Section: Discussionmentioning
confidence: 99%
“…The results are sensitive to the sepsis incidence, which, as discussed by Bray et al, 16 depends, among other things, on how sepsis is diagnosed in the clinic. A broad definition of sepsis leads to a higher incidence, and a prediction algorithm would thus have a larger potential of reducing costs in situations where a broader definition is used.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…In this study, we investigated the cost-saving potential of a machine learning algorithm such as NAVOY® Sepsis for early detection of sepsis in intensive care units (ICUs) in Sweden. Since the evaluation of costs and cost-effectiveness of novel diagnostic tools depend on multiple factors such as the definition of sepsis, the diagnostic tool currently used, and the sensitivity and specificity of the diagnostic tool, 16 we aimed at developing a health economic model that would enable us to simulate the cost-saving potential of a sepsis prediction algorithm in various contexts.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%
“…One-sixth of survivors experience post-sepsis syndrome with at least one cognitive, psychological, or physical impairment, and indeed are more prone to recurrent infection, renal failure, and cardiovascular episodes than matched patients hospitalised for other diagnoses [ 17 ]. As such, sepsis poses a significant medical and financial burden on healthcare services worldwide, with the National Health Service in the United Kingdom alone estimated to face annual costs of >£1 billion [ 19 ]. Although late-mortality and long-term symptoms following sepsis are well-studied, the causes of sequelae are poorly understood [ 20 ].…”
Section: Sepsismentioning
confidence: 99%